2021
DOI: 10.1002/jcb.29916
|View full text |Cite
|
Sign up to set email alerts
|

Dual inhibition of MEK1/2 and MEK5 suppresses the EMT/migration axis in triple‐negative breast cancer through FRA‐1 regulation

Abstract: Triple‐negative breast cancer (TNBC) presents a clinical challenge due to the aggressive nature of the disease and a lack of targeted therapies. Constitutive activation of the mitogen‐activated protein kinase (MAPK)/extracellular signal‐regulated kinase (ERK) pathway has been linked to chemoresistance and metastatic progression through distinct mechanisms, including activation of epithelial‐to‐mesenchymal transition (EMT) when cells adopt a motile and invasive phenotype through loss of epithelial markers (CDH1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…In triple negative breast cancer (TNBC) cells, Hoang et al showed that the inhibition of MEK1/2 and MEK5 using a pan-MEKi drastically decreased the migration potential of the cells compared to MEK1/2 or MEK5 inhibition alone. Even though the authors failed to show the comparative differences in vivo, the employed pan-MEKi SC-151 was effective in reducing cell viability, cellular migration, and invasion in a sub-group of aggressive TNBC cell lines [ 127 ].…”
Section: Erk5 In Mechanical Stress-exposed Tissues and Mapk Inhibitor-resistant Cancersmentioning
confidence: 99%
“…In triple negative breast cancer (TNBC) cells, Hoang et al showed that the inhibition of MEK1/2 and MEK5 using a pan-MEKi drastically decreased the migration potential of the cells compared to MEK1/2 or MEK5 inhibition alone. Even though the authors failed to show the comparative differences in vivo, the employed pan-MEKi SC-151 was effective in reducing cell viability, cellular migration, and invasion in a sub-group of aggressive TNBC cell lines [ 127 ].…”
Section: Erk5 In Mechanical Stress-exposed Tissues and Mapk Inhibitor-resistant Cancersmentioning
confidence: 99%
“…One such targeted therapy involved a combinational therapy of RAF/MEK inhibitor CH5126766 alongside Eribulin in TNBC and it was observed that this combinational mechanism was successful in inhibiting apoptosis and cell migration, thus contributing to tumor growth 68 . In another study, dual inhibition of MEK1/2 and MEK 5 by using inhibitors Cobimetinib and Trametinib resulted in the suppression of EMT in triple negative breast cancer 69 . Mohan et al have also shown that Brucein D (BD) which is an inhibitor targeting the p38 pathway lead to apoptosis and decrease viability of the breast cancer cells induced by the MAPK pathway 70 .…”
Section: Potential Treatments Targeting Cell-intrinsic Pathways Media...mentioning
confidence: 98%
“…One such targeted therapy involved a combinational therapy of RAF/MEK inhibitor CH5126766 with eribulin in TNBC that successfully in inhibiting apoptosis and cell migration, thus contributing to tumor growth [89]. In another study, dual inhibition of MEK1/2 and MEK 5 using inhibitors cobimetinib and trametinib resulted in the suppression of EMT in TNBC [90]. Mohan et al.…”
Section: Potential Treatments Targeting Cell‐intrinsic Pathways Media...mentioning
confidence: 99%
“…One such targeted therapy involved a combinational therapy of RAF/MEK inhibitor CH5126766 with eribulin in TNBC that successfully in inhibiting apoptosis and cell migration, thus contributing to tumor growth [89]. In another study, dual inhibition of MEK1/2 and MEK 5 using inhibitors cobimetinib and trametinib resulted in the suppression of EMT in TNBC [90]. Mohan et al have also shown that brucein D, which is an inhibitor targeting the p38 pathway leads to apoptosis and decreases the viability of breast cancer cells by inhibiting the MAPK pathway [91].…”
Section: Potential Treatments Targeting Cell-intrinsic Pathways Media...mentioning
confidence: 99%